WINTER WHEAT PRODUCTIVITY AND MOISTURE RESERVES - E. A. Gaevaya; A. E. Mishchenko (Зерновое хозяйство России)
The article gives a summary of the results of study of hydrothermal conditions of winter wheat cultivation on the slopes of the Rostov region. In the analysis of atmospheric precipitations and average daily temperatures we calculated a hydrothermal coefficient of G.T. Selyaninov. We carried out the research of the past few years taking into consideration their hydrothermal coefficient and divided them on very dry, dry, slightly dry and wet years. The distribution of moisture reserves was studied depending on the conditions of moisture supply in a cold period of the year in 0-100 cm of soil, bare (autumn) fallow, for winter wheat in a fallow land and for winter wheat sown after winter wheat.  It was carried out an analysis of precipitations’ accumulation in a cold period of the year at different agricultural backgrounds. It was revealed that a primary accumulation of moisture in the fields occurs in a cold period of the year (41,4-53,5% of all moisture reserves of the year). We found dependence between a moisture reserve in a sowing layer and field germination of winter wheat seeds, sown after different predecessors on the slopes subject to erosion. It has been found out that sprouts do not appear if moisture reserves in an arable layer are 1,3-9,4 mm; their condition is very poor if moisture reserves are 12-19 mm; moisture reserves of 20 mm give satisfactory sprouts and moisture reserves of more than 20 mm give good sprouts. The correlation between winter wheat productivity and moisture reserves in an arable layer has been defined. The article gives the results of winter wheat productivity sown after different predecessors and after various amounts of organic-mineral fertilizing and it gives the calculation of its water consumption coefficient.